Use of Resin Infiltrant to Prevent Discoloration after Teeth Whitening - Ji-Hyun Min (치위생과학회지, 2022)
Background: This study attempted to apply resin infiltrant (RI) as a method to maintain the effect of tooth bleaching treatment and compared it with fluoride varnish (FV) or artificial saliva to evaluate the effect.Methods: Sixty healthy lozenge specimens were classified into five groups. Group 1 was the negative control group, and discoloration was induced after artificial saliva treatment of the tooth specimen (G1S+C). Group 2 was a positive control group, in which pigmentation was induced after bleaching treatment and artificial saliva treatment (G2B+S+C). Coloration was induced in group 3 (experimental group 1) after bleaching treatment and artificial saliva treatment, followed by application of fluorine varnish (G3B+FV+S+C). Coloration was induced in Group 4 (experimental group 2) after applying RI after bleaching treatment and artificial saliva treatment (G4B+RI+S+C). Pigmentation was induced in group 5 (experimental group 3) after bleaching treatment and artificial saliva treatment, followed by acid treatment (etching) and treatment with RI (G5B+E+RI+S+C). Coffee and wine were used to induce discoloration. The lightness value (L*) of the CIE L*a*b* color system was obtained by image analysis. Kruskal–Wallis H analysis was performed for the mean difference in L* values by group.Results: When coloration was induced with coffee, there was no significant difference in L* value between artificial saliva (G2B+S+C), FV (G3B+FV+S+C), and RI (G4B+RI+S+C, G5B+E+RI+S+C) groups. There was no significant difference in L* values between the artificial saliva (G2B+S+C), FV (G3B+FV+S+C), and RI (G4B+RI+S+C, G5B+E+RI+S+C) groups, even in the case of wine induced coloration.Conclusion: It was confirmed that artificial saliva or RI treatment had similar effects to the FV previously used to maintain the effect of tooth bleaching treatment.